2003
DOI: 10.1038/sj.ijir.3901097
|View full text |Cite
|
Sign up to set email alerts
|

Sex steroid hormones differentially regulate nitric oxide synthase and arginase activities in the proximal and distal rabbit vagina

Abstract: Nitric oxide synthase (NOS) and arginase have been shown to regulate nitric oxide (NO) production reciprocally in genital tissues. In animal models, NO is an important regulator of vaginal blood flow and vaginal wall contractility. In this study, we investigated the modulation of NOS and arginase activities by estrogens and androgens in the proximal and distal rabbit vagina. In intact control animals, total NOS activity was higher in the proximal (528 7 78 pmol/mg protein) than the distal (391 7 44 pmol/mg pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 43 publications
2
33
0
Order By: Relevance
“…For instance, arginase is increased in diabetic blood vessels, and the deficit in NO is normalized by adding an arginase inhibitor (Romero et al, 2008). Because estrogens positively regulate arginase expression and activity in nonvascular tissues (Traish et al, 2003), some of our results on NO production could be interpreted by differences in ER␣-versus ER␤-mediated differences in arginase expression.…”
Section: Discussionmentioning
confidence: 93%
“…For instance, arginase is increased in diabetic blood vessels, and the deficit in NO is normalized by adding an arginase inhibitor (Romero et al, 2008). Because estrogens positively regulate arginase expression and activity in nonvascular tissues (Traish et al, 2003), some of our results on NO production could be interpreted by differences in ER␣-versus ER␤-mediated differences in arginase expression.…”
Section: Discussionmentioning
confidence: 93%
“…A number of studies have demonstrated that ovarian steroids regulate NO and NOS synthesis in various cells and organs [16,25,26,29,35]. In the rat uterus, estradiol-17 inhibits iNOS and stimulates eNOS gene expression [32].…”
Section: Discussionmentioning
confidence: 99%
“…Because estrogens are known to modulate the expression of nNOS in several target organs, such as the hypothalamus (33) and genital tract (30), we explored the effects of supraestrus levels of E 2 on lower urinary tract function and morphology and urethral nNOS expression, as well as the consequences of acute inhibition of nNOS activity by 7-nitroindazole.…”
mentioning
confidence: 99%